Correlation between Oxygen Demand of Nematode Communities with Dissolved Oxygen in the Organic Shrimp Farming Ponds, Ca Mau Province - Thai, Tran Thanh; Lam, Nguyen Le Que; Yen, Nguyen Thi My; Quang, Ngo Xuan (VNU Journal of Science: Natural Sciences and Technology, 2018)
Dissolved oxygen (DO), total biomass and oxygen demand of nematode communities in the organic shrimp farms located in Tam Giang commune, Nam Can District, Ca Mau province were investigated in three seasons (March-dry, July-transfer and November-wet season) of 2015. The results showed that most of DO values were within permissible limits. However, the frequency distributions of DO values are very compressed at the lower limit of their scale. Total dry biomass varied from 24.77 to 937.04 µgC/10cm 2 while oxygen demand ranged from 3467.39 to 64288.50 nlO2/day/10cm 2 . These values were slightly high when compared to other studies in the world. The following results recorded that the negatively correlation between DO and oxygen demand of nematode communities in the organic shrimp farms. This may well suggest that respiration and metabolic of nematode communities was high and their impact on oxygen dissolved in surface water. Keywords Biomass, dissolved oxygen, Ca Mau, nematode communities, organic shrimp farms, oxgen demand References [1]. P. N. Hong, H. T. San, Mangroves of Vietnam 7 (1993) IUCN. [2]. T. Nga, Hệ thống rừng-tôm trong phát triển bền vững vùng ven biển đồng bằng sông Cửu Long. Tạp chí Khoa học Trường Đại học Cần Thơ 10 (2008) 6. [3]. Thai agricutural standard (TAS), Organic marine shrimp farming, Royal Gazette 124 (2007) Section 78E. [4]. T. T. Thai, N. T. My Yen, N. Tho, N. X. Quang, Meiofauna in the mangrove–shrimp farms ponds, Ca Mau province. Journal of Science and Technology 55(2017) 271. [5]. L. Marte, The Food and Feeding Habit of Penaeus Monodon Fabricius Collected From Makato River, Aklan, Philippines (Decapoda Natantia) 1, Crustaceana 38(1980) 225. [6]. N. Majdi, W. Traunspurger, Free-living nematodes in the freshwater food web: a review, Journal of nematology 47 (2015) 28. [7]. M. C. Austen, Natural nematode communities are useful tools to address ecological and applied questions, Nematology Monographs and Perspectives 2 (2004) 1. [8]. F. Boufahja, H. Beyrem, N. Essid, J. Amorri, E. Mahmoudi, P. Aissa, Morphometry, energetics and diversity of free-living nematodes from coasts of Bizerte lagoon (Tunisia): an ecological meaning, Cahiers de biologie marine 48 (2007) 121. [9]. Ministry of Agriculture and Rural development, 2016. https://tongcucthuysan.gov.vn/en-us/aquaculture/doc-tin/006222/2016-10-28/ca-mau-set-outs-to-become-viet-nams-largest-shrimp-hub. Truy cập ngày 14/8/2017. [10]. M. Vincx, Meiofauna in marine and freshwater sediments, In G. S. Hall (Ed.), Methods for the examination of organismal diversity in soils and sediments Wallinfort, UK, 1996. [11]. A. T. De Grisse, Redescription ou modifications de quelques technique utilis [a] es dan l'etude des n [a] ematodes phytoparasitaires (1969). [12]. R.M. Warwick, H.M. Platt, P.J. Somerfield, Free living marine nematodes. Part III. Monhysterids. The Linnean Society of London and the Estuarine and Coastal Sciences Association, London 1988. [13]. Zullini, The Identification manual for freshwater nematode genera, Lecture book, MSc Nematology Ghent University 2005. [14]. N. V. Thanh, Giun tròn sống tự do Monhysterida, Araeolaimida, Chromadorida, Rhabditida, Enoplida, Mononchida, Dorylaimida. Động vật chí Việt Nam. Hà Nội: Nhà xuât ba̓n khoa học và kỹ thuật, 22, 2007 455. [15]. J. Vanaverbeke, T.N. Bezerra, U. Braeckman, A. De Groote, N. De Meester, T. Deprez, S. Derycke, K. Guilini, F. Hauquier, L. Lins, T. Maria, T. Moens, E. Pape, N. Smol, , M. Taheri, J. Van Campenhout, A. Vanreusel, X. Wu, M. Vincx, (2015) NeMys: World Database of Free-Living Marine Nematodes. Accessed at http://nemys.ugent.be on 2017. [16]. H. M. Platt, R. M. Warwick, Freeliving marine nematodes. Part 1: British enoplids. Pictorial key to world genera and notes for the identification of British species. Cambridge University Press, for the Linnean Society of London and the Estuarine and Brackish-water Sciences Association 1983. [17]. Andrassy I The determination of volume and weight of nematodes, Acta Zoologica 2 (1956) 1. [18]. J. Vanaverbeke, P. M. Arbizu, H. U. Dahms, H. K. Schminke,. The metazoan meiobenthos along a depth gradient in the Arctic Laptev Sea with special attention to nematode communities, Polar Biology 18 (1997) 391. [19]. K. Soetaert, J. Vanaverbeke, C. Heip, P. M. Herman, J. J. Middelburg, A. Sandee, G. Duineveld, Nematode distribution in ocean margin sediments of the Goban Spur (northeast Atlantic) in relation to sediment geochemistry, Deep Sea Research Part I: Oceanographic Research Papers, 44 (1997) 1671. [20]. D.J. Crisp Methods of the study of marine benthos (N.A. Holme & A.D. McIntyre eds), Blackwell Scientific Publications, Oxford, 1971 197. [21]. N. Smol, K. A. Willems, J. C. Govaere, A. J. J. Sandee, Composition, distribution and biomass of meiobenthos in the Oosterschelde estuary (SW Netherlands). In The Oosterschelde Estuary (The Netherlands): a Case-Study of a Changing Ecosystem, Springer Netherlands (1994) 197. [22]. H. Dye, An Ecophysiological Study of the Meiofauna of the Swartkops Estuary, African Zoology 13(1978) 1. [23]. Van Damme, R. Herman, Y. Sharma, M. Holvoet, P. Martens, Benthic studies of the Southern Bight of the North Sea and its adjacent continental estuaries, Progress Report II. Fluctuations of the meiobenthic communities in the Westerschelde estuary. ICES. CM/L, 23 (1980) 131. [24]. Q. X. Ngo, C. Nguyen Ngoc, A. Vanreusel, Nematode morphometry and biomass patterns in relation to community characteristics and environmental variables in the Mekong Delta, Vietnam, Raffles Bulletin of Zoology 62 (2014) 501. [25]. J. M. Whetstone, G. D. Treece, C. L. Browdy, A. D. Stokes, Opportunities and constraints in marine shrimp farming, South Regional Aquaculture Center 2002.